Acute Inhibition of PKA Activity at Old Ages Ameliorates Age-Related Memory Impairment in Drosophila. - Yamazaki, D.; Horiuchi, J.; Miyashita, T.; Saitoe, M. (Journal of Neuroscience, 2010)
Age-related memory impairment (AMI) is a critical and debilitating phenotype of brain aging, but its underlying molecular mechanisms are largely unknown. In Drosophila, AMI is highly correlated with PKA activity in the mushroom bodies, neural centers essential for forming associative olfactory memories. Heterozygous mutations in DC0 (DC0/+), which encodes the major catalytic subunit of PKA (PKAc), significantly suppress AMI, while overexpression of a DC0 transgene (DC0(+)) impairs memory and occludes AMI. PKA activity does not increase upon aging, and it is not clear whether AMI is caused by continual PKA activity throughout aging or by an acute increase in PKA signaling at old ages. Likewise, it is not clear whether AMI can be ameliorated by acute interventions at old ages or whether continuous intervention throughout aging is necessary. We show here that an acute increase in PKA activity at old ages is sufficient to restore normal AMI in DC0/+ flies. Conversely, acute expression of a PKA inhibitory peptide at old ages is sufficient to reverse AMI in a wild-type background. These results indicate that AMI in Drosophila is caused by an age-dependent change in PKA-dependent signaling that can be reversed by acute interventions at old ages.